Perilaku Kreatif Pekerja Call Center: Peran Komunikasi dan Dukungan Training Center - Nugroho J. Setiadi (Bina Nusantara University, 2013)
Call center business in Indonesia is growing rapidly worldwide. This condition has had repercussions for a growing number of call center workers needed. They are forced to be more creative in performing their duties. This study aims to determine the role of communication and training center in supporting the creative performance of workers in call centers. The survey was conducted by distributing questionnaires to 100 respondents (employees) of the 3 major companies in the field of telecommunication services in Indonesia. Regression analysis was used to analyze the data to examine the role of communication and training support center on creative performance. The results indicated that communication and training support center significantly influence the creative behavior in call center workers. Communication quality shown in the telecommunication service provider companies, such as the media quality, simplicity of information, dissemination of information, loads of information, and accuracy of messages, has shown good quality. In addition, the training program has shown its support for call center workers in the form of program effectiveness through research and data collection, determining the materials, training methods, choosing a coach, preparing facilities, selecting and implementing the program.